Exploring the potentials of Sesuvium portulacastrum L. for edibility and bioremediation of saline soils - Zhang, Wenbin; Wang, Dan; Cao, Dingding; Chen, Jianjun; Wei, Xiangying (Frontiers in Plant Science, 2024)
Sesuvium portulacastrum L. is a flowering succulent halophyte in the ice plant family Aizoaceae. There are various ecotypes distributed in sandy coastline and salty marshlands in tropical and subtropical regions with a common name of sea purslane. Plants are tolerant to salt, and drought, and flooding stresses and have been used for salt alkali soisand dune stabilization and l restoration of and sand fixation in coastal areas. With increased salinization of agricultural soils and widespread pollution of toxic metals in the environment and excessive nutrients in water bodies, S. portulacastrum has been explored for desalination of saline soils and phytoremediation of metals from contaminated soils and nitrogen and phosphorus from eutrophic water. Additionally, sea purslane has nutraceutical and pharmaceutical value. Tissue analysis indicates that plants are rich in carbohydrates, proteins, vitamins, and mineral nutrients. Florida's native Americans ate it raw, pickled, or cooked. In the Philippines, it is known as atchara after being pickled. S. portulacastrum contains high levels of ecydsteroids, which possess antidiabetic, anticancer, and anti-inflammatory activities in mammals. Florida's native Americans ate it raw, pickled, or cooked. In the Philippines, it is known as atchara after being pickled. Tissue analysis indicates that plants are rich in carbohydrates, proteins, and mineral nutrients but sea purslane plants have not been widely recognized as edible plants. In this review article, we present botanical information, physiological and molecular mechanisms underlying their tolerance of sea purslane plants to different stresses, their nutritional and pharmaceutical values, and methods for propagation and production of sea purslane plants in saline soils and waterbodies. Their adaptability to a wide range of stressful environments and production of valuable bioactive compounds suggest that S. portulacastrum plants are valuable genetic resources that can be used for bioremediation of soil salinity and eutrophic water, and produced in saline soils as a leafy vegetable and also be used for bioremediation of soil salinity.